THE RESEARCH OF SEMANTIC SPACE OF BRAND - I. Alexandrova (Вестник университета)
Held socio-psychological analysis of the phenomenon of consumer perceptions of the brand. The author's definition of «consumer perception of the brand», «brand semantic space». The author's projective technique of qualitative social research, aimed at the reconstruction of the semantic space of the brand.